READINESS TO TAKE RE-TEST - FIRST YEAR MBBS STUDENT VIEW - GARA, RAMADEVI; RAO, RAPETIRAMANA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: During COVID-19 pandemic, there were many changes adopted in medical education, most of the syllabus (theory and practical) was taught in online. During this online classes, 1st year MBBS students were the most affected, because they are new to curriculum, difficult to adopt the transition from intermediate to under graduation course, this created lot of pressure in the students. Once the students are back for offline classes, we have conducted internal assessment test after a month of offline classes and the test results were poor. Main objective of this study is to see the relationship between conducting retest and improving the academic performance and to record the student view on retest. Methods: Sample size for the 1st test (n-149) and 2nd test (n-141). We have given Google form with ten questions, out which responses were recorded based on Likert 4 point scale. Results: The repeat exam provided immediate reward for using the initial exam as a study guide. When we compared the results of test and retest, there was great improvement in score. Conclusion: Retest helped to reduce test anxiety and to encourage the learning of course material. It helped the faculty to fill the lacunae to improve the further outcome.